(untitled) (Modern education and development, 2025)
Valeology, derived from the Latin "valeo" meaning "to be healthy", is the interdisciplinary science of health and healthy living. It combines elements of medicine, psychology, pedagogy, and social sciences to study human health, its maintenance, and promotion. This article explores the foundations of valeology, its key principles, and its relevance in contemporary medical practice, especially in disease prevention, health promotion, and patient education.